1997
DOI: 10.21236/ada406400
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Vibratory Loads Data from a Wind-Tunnel Test of a Model Helicopter Main-Rotor Blade with a Paddle-Type Tip

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…The geometric properties of the four rotor blades considered within this paper are described here: the Langley Baseline (LBL) and Langley BERP blades (LBERP) [43], PSP rotor [42], and the XV-15 tiltrotor blade [44].…”
Section: Blade Geometriesmentioning
confidence: 99%
See 2 more Smart Citations
“…The geometric properties of the four rotor blades considered within this paper are described here: the Langley Baseline (LBL) and Langley BERP blades (LBERP) [43], PSP rotor [42], and the XV-15 tiltrotor blade [44].…”
Section: Blade Geometriesmentioning
confidence: 99%
“…The main aim of the selected computations is to cover a variety of collectives, tip Mach numbers and blade geometries. Further information on the exact experimental conditions can be found in the respective references for each rotor blade design: XV-15 [44], PSP [12,42], Langley Baseline (LBL) and Langley BERP (LBERP) [43].…”
Section: Computational Setup and Test Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 are the subject of this study: the Langley Baseline blade (LBL) with a rectangular planform, the Langley BERP blade (LBERP) with a paddle-shaped tip and the PSP blade with a swept-tapered blade tip and a scaled Langley Baseline blade (LBLs) to examine solidity effects. The LBERP and LBL blades were tested by Yeager et al (6) at model scale in a Freon-12 medium with a higher density than air. This allowed tests closer to full scale Reynolds numbers.…”
Section: Blade Geometriesmentioning
confidence: 99%
“…Despite the findings of Perry (5) , the thrust-weighted solidity parameter (or equivalent rectangular blade), continues to be used in many rotor design studies found in literature. The experiments by Yeager et al (6) , matched the thrust-weighted solidity between a rectangular and BERP planform. Various optimisation studies have also kept this parameter constant (7)(8)(9) , which leads to favourable treatment of planforms with lower blade area across the blade tip, as seen by Perry (5) for the BERP and tapered planforms.…”
Section: Introductionmentioning
confidence: 99%